Hydraulic Conductivity of a Firn Aquifer in Southeast Greenland - Miller, Olivia L.; Solomon, D. Kip; Miège, Clément; Koenig, Lora S.; Forster, Richard R.; Montgomery, Lynn N.; Schmerr, Nicholas; Ligtenberg, Stefan R. M.; Legchenko, Anatoly; Brucker, Ludovic (Frontiers in Earth Science, 2017)
Some regions of the Greenland ice sheet, where snow accumulation and melt rates are high, currently retain substantial volumes of liquid water within the firn pore space throughout the year. These firn aquifers, found between ~10 and 30 m below the snow surface, may significantly affect sea level rise by storing or draining surface meltwater. The hydraulic gradient and the hydraulic conductivity control flow of meltwater through the firn. Here we describe the hydraulic conductivity of the firn aquifer estimated from slug tests and aquifer tests at six sites located upstream of Helheim Glacier in southeastern Greenland. We conducted slug tests using a novel instrument, a piezometer with a heated tip that melts itself into the ice sheet. Hydraulic conductivity ranges between 2.5 × 10−5 and 1.1 × 10−3 m/s. The geometric mean of hydraulic conductivity of the aquifer is 2.7 × 10−4 m/s with a geometric standard deviation of 1.4 from both depth specific slug tests (analyzed using the Hvorslev method) and aquifer tests during the recovery period. Hydraulic conductivity is relatively consistent between boreholes and only decreases slightly with depth. The hydraulic conductivity of the firn aquifer is crucial for determining flow rates and patterns within the aquifer, which inform hydrologic models of the aquifer, its relation to the broader glacial hydrologic system, and its effect on sea level rise.